Omphalocele and gastroschisis: comparison of outcome in a resource limited tertiary centre - Samiul Hasan; Ashrarur Rahman Mitul; Ayub Ali; KMN Ferdous; Umama Huq (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2018)
Background. Neonates with gastroschisis are expected to have better prognosis than omphalocele as the latter is commonly associated with other congenital anomalies. But in our centre, we experience the opposite scenario regarding outcome. The aim of this study was to compare the outcome of these two conditions and to some extent to identify the factors influencing the consequences. Methods. It was a prospective observational study done at Dhaka Shishu (Children) Hospital from June 2017 to November 2017. All neonates admitted with omphalocele and gastroschisis during the study period were included. Data were collected in a structured questionnaire. Results. Total number of cases were 38 (24 omphalocele & 14 gastroschisis). None of the patients were antenatally diagnosed. Gender, mean birth weight, mean gestational age, maternal age and mode of delivery demonstrated inconsiderable influence on the outcome. Out of 24 patients with omphalocele, in 20 patients, it was associated with other anomalies, and the other 4 patients died before evaluation. Mortality rate was significantly higher in gastroschisis (86%) than with omphalocele (42%). Conclusion. Inadequate perinatal management contributes to the poorer prognosis of gastroschisis in our centre. Antenatal diagnosis, planned delivery and appropriate management in immediate post natal period can improve the result of these conditions.